Field Abundance Patterns and Odor-Mediated Host Choice by Clover Seed Weevils, Apion fulvipes and Apion trifolii (Coleoptera: Apionidae) - Nyabuga, Franklin N. (My University, 2015)
The clover seed weevils Apion fulvipes Geoffroy, 1785 and Apion trifolii L., 1768 (Coleoptera: Apionidae) cause major losses to seed production of white clover (Trifolium repens L.) and red clover (Trifolium pratense L.), respectively. Clover is important as animal forage and an alternative to inorganic fertilizers. Because clover is mainly pollinated by bees, the use of insecticides in management of these weevils is discouraged. To gain basic knowledge for development of alternative management strategies, we investigated weevil field abundance over two growing seasons, as well as feeding and olfactory host preferences by A. fulvipes and A. trifolii. Field trap catches in southern Sweden revealed that white clover was dominated by A. fulvipes and red clover by A. trifolii. For both weevil species, female catches were positively correlated to the number of clover buds and flowers in the field. In feeding and olfactory bioassays, females of A. fulvipes and A. trifolii showed a preference for T. repens and T. pratense, respectively. However, the feeding preference was lost when the antennae were removed, indicating a significant role of olfaction in host choice. Male weevils of both species did not show clear olfactory or feeding preferences for host plant species. The field study and laboratory bioassays demonstrate that, at least for female weevils, olfaction is important for selection of host plants.We discuss these novel results in the context of managing these important pests of clover by exploiting olfaction and behavioral attraction to host plant volatiles.
Keywords: Trifolium repens; Trifolium pratense; olfaction; feeding; behavior manipulation